2017
DOI: 10.1167/iovs.16-20539
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E2 and E3, but Not E4, Promote Retinal Pathologic Neovascularization

Abstract: These results demonstrate that ApoE2 and ApoE3, but not ApoE4, have proangiogenic effects, and the increased expression of ApoE in the vitreous humor of patients with PDR and DME indicates that ApoE2 and ApoE3 are involved in the development of retinal neovascularization in eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Moreover, the harmful effect of APOE 4 has been associated not only to a higher risk of AD but also to a higher risk or different clinical outcomes for other neurological [195198] and non-neurological conditions [199203]. These latter findings support the hypothesis that APOE is very much indeed a possible general modifier of various biological and consequently, clinical phenomena.…”
Section: Apoe Polymorphism In Normal and Pathologic Conditions Of Thementioning
confidence: 57%
“…Moreover, the harmful effect of APOE 4 has been associated not only to a higher risk of AD but also to a higher risk or different clinical outcomes for other neurological [195198] and non-neurological conditions [199203]. These latter findings support the hypothesis that APOE is very much indeed a possible general modifier of various biological and consequently, clinical phenomena.…”
Section: Apoe Polymorphism In Normal and Pathologic Conditions Of Thementioning
confidence: 57%
“…This determined that ApoE4 has transitory synaptic and vascular effects during retinal development, before and after the neonatal period, respectively. Moreover, VEGF in aged retina has proangiogenic effects that promote macular edema, diabetic retinopathy, and macular holes [ 89 , 90 ].…”
Section: Pathological Mechanisms Of a β And Taumentioning
confidence: 99%
“…ApoE can be expressed in RPE, GCL, and BM and is synthesized in Müller cells [ 89 ]. ApoE is involved in uptake, processing, transport, and clearance of lipids for retinal metabolism; therefore, disturbance of this process may lead to cholesterol and lipid accumulation in BM [ 43 ].…”
Section: Pathological Mechanisms Of a β And Taumentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and cellular model studies revealed that APOE4 is associated with impaired cellular plasticity [32, 34, 35]. It is thus likely that the negative effects of APOE4 in AD are due to this impaired neuronal synaptic plasticity, whereas in AMD, in which the key pathology is increased angiogenesis and vascular plasticity, the effects of apoE4 could be protective due to the reduction in retinal pathological neovascularization [36].…”
Section: Introductionmentioning
confidence: 99%